Ultra-processed food consumption affects structural integrity of feeding-related brain regions independent of and via adiposity - Filip Morys; Arsene Kanyamibwa; Daniel Fängström; Max Tweedale; Alexandre Pastor-Bernier; Houman Azizi; Lang Liu; Annette Horstmann; Alain Dagher (npj Metabolic Health and Disease)
Abstract Consumption of ultra-processed foods (UPFs) increases overall caloric intake and is associated with obesity, cardiovascular disease, and brain pathology. There is scant evidence as to why UPF consumption leads to increased caloric intake and whether the negative health consequences are due to adiposity or characteristics of UPFs. Using the UK Biobank sample, we probed the associations between UPF consumption, adiposity, metabolism, and brain structure. Our analysis reveals that high UPF intake is linked to adverse adiposity and metabolic profiles, alongside cellularity changes in feeding-related subcortical brain areas. These are partially mediated by dyslipidemia, systemic inflammation and body mass index, suggesting that UPFs exert effects on the brain beyond just contributing to obesity. This dysregulation of the network of subcortical feeding-related brain structures may create a self-reinforcing cycle of increased UPF consumption.